Transborder labour liberalization: a path to enforcement of the global social contract for labour - Bravo, K (Foundation for Law, Justice and Society, 2009)
The failure of international trade law to liberalize labour stands in stark contradiction to the liberalization of other fundamental economic inputs, and undermines the vision for a globalized world. The transnational labour market is characterized by the illegality and temporariness that is assigned by states to mobile and would-be mobile human providers of labour; yet the globalized transnational economy stimulates, and indeed demands, the movement of labour from one domestic economy to another. The disjuncture and disequilibrium arising from the interaction of international trade law and domestic immigration law, which seeks to barricade domestic markets from the entry of human transborder labour providers, are in conflict with the reality of transnational economic forces. Consequently, they foster illegal transborder movements that greatly increase the vulnerability to exploitation of mobile human would-be labour providers. The proposed liberalization of labour would make both the international human rights and multilateral trade regimes more consistent with human (and labour) rights ideals.